Use of Telone II and Temik 15G to Improve Yields and Returns of Cotton Grown in Northwest Florida Fields Infested with Root-Knot Nematodes - D. J. Zimet; J. L. Smith; R. A. Kinloch; Jimmy R. Rich; Timothy D. Hewitt (EDIS)
In Florida, nematicides are the most viable nematode management option because many growers only produce monoculture cotton and the low prices of other agronomic crops in the state make crop rotation expensive. The two primary nematicides used and recommended in Florida are Telone II and Temik 15G (Kinloch and Rich, 2000). This is EDIS document FE 318, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published November 2004.